Efficacy of Covid-19 Mitigation Strategies on Incidence - Aljehany, Jamil; Alzarfani, Sultan; Alharbi, Mohammed (International Journal of Innovative Research in Medical Science, 2025)
This study aims at assessing the efficacy of COVID-19 mitigation strategies on incidence. It examines the efficacy of the test-trace-isolate-quarantine (TTIQ) strategy in the containment of COVID-19 pandemic to determine the role of the environment in the pandemic and to recommend appropriate practices in the management of COVID-19 outbreak in terms of contact tracing, screening, quarantine, and isolation. To achieve these objectives, the study uses the systematic literature review, whereby secondary data is utilised to address the problem. The study findings show that TTIQ is the best practice for application by medical healthcare practitioners to treat COVID-19 cases worldwide. The TTIQ approach positively impacts the efforts to contain the virus due to the structured measures and practices utilized in dealing with the pandemic. However, the specific characteristics of the environment such as the presence of the supporting healthcare practitioners, defined procedures for minimal interactions and the general application of the related best practices affect the outcome of the exercise and the effectiveness of the TTIQ. In the same way, the presence of qualified practitioners is critical in delivering the required guidelines and expected outcomes towards the containment of the virus. Consequently, the efforts to improve environmental characteristics significantly help in achieving the best outcomes in containing the virus by introducing the cases of infection and achieving high-quality care for infected patients. The need to embrace solutions that minimize the physical interactions and improve the efficacy of the strategies of the management of the pandemic necessitated the adoption of the digital solutions; which mainly consisted of the mobile app solutions and the website technologies to support the strategies implemented to the population.